2014
DOI: 10.1080/10408398.2011.652316
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Analysis of Bioactive Compounds inCapsicumPeppers

Abstract: An overview of the state of the art in the extraction, isolation, and analytical determination of bioactive compounds in peppers of the genus Capsicum is presented. The review is structured by classes of phytochemicals. Both major and minor constituents of peppers are considered. Modern trends in analytical chemistry of nutrients in regard to pepper analysis with particular focus on chromatographic and related methods are discussed. Attention was paid to controversial questions of pepper analysis, including bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 250 publications
1
35
2
Order By: Relevance
“…It can be concluded that capsaicinoids and AsA are responsible for antioxidant activity of highly pungent peppers such as 'Jolokia' under the conditions of our experiment, although the importance of phenolic compounds in the contribution to the total antioxidant activity of peppers, suggested by Bogusz et al [37], could be significant in mildly pungent genotypes such as 'Aji Lemon Drop'. Asnin and Park [38] stated that the capsaicin profile did not directly reflect antioxidant activity, due to the presence of other antioxidant compounds, i.e., phenolics. Moreover, phenolic compounds, because of their antioxidant activity, can play a certain role in the prevention of civilisational diseases.…”
Section: Stress Parameters Of Chilli Pepper Fruits and Leavesmentioning
confidence: 99%
“…It can be concluded that capsaicinoids and AsA are responsible for antioxidant activity of highly pungent peppers such as 'Jolokia' under the conditions of our experiment, although the importance of phenolic compounds in the contribution to the total antioxidant activity of peppers, suggested by Bogusz et al [37], could be significant in mildly pungent genotypes such as 'Aji Lemon Drop'. Asnin and Park [38] stated that the capsaicin profile did not directly reflect antioxidant activity, due to the presence of other antioxidant compounds, i.e., phenolics. Moreover, phenolic compounds, because of their antioxidant activity, can play a certain role in the prevention of civilisational diseases.…”
Section: Stress Parameters Of Chilli Pepper Fruits and Leavesmentioning
confidence: 99%
“…The separation of seed and pulps can be useful to evaluate the distribution of capsainoids in the fruits. Moreover, it should be stressed that capsaicinoids and phenolics are biosynthetically derived from the phenylpropanoid pathway and that both possess antioxidant activities (Asnin and Park 2015). This particularity makes it important to correlate the contents of capsaicin and dihidrocapsaicin with the phenolic contents and antioxidant capacities of both pulp and seed extracts.…”
Section: Introductionmentioning
confidence: 99%
“…), are grown worldwide, used extensively as a natural food colorant and seasoning agent due to their attractive color, flavor, and taste (ReyesEscogido et al 2011). Pepper has a high nutritive value and has long been recognized as an excellent source of vitamin C, carotenoids, phenolic compounds and other phytochemicals that are powerful antioxidants that destroy free radicals (Asnin and Park 2015;Kothari et al 2010). The levels of these compounds in pepper depend on many factors, including cultivar, maturity, growing conditions, and climate (Menichini et al 2009;Zhuang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Oleoresins contain a significant amount of esters of capsorubin, capsanthin, cryptoxanthin, zeaxanthin, and other carotenoids [70,71], used in foodstuff and cosmetics, and serve as a source of the pungent component capsaicin for pharmaceutical products [72,73] or self-defense weaponry [74]. Bioactive compounds present in Capsicum fruits display antioxidant, anticancer, anti-inflammatory, antiulcer, and antiobesity pharmaceutical properties, among others, and they also promise other health benefits [75]. Furthermore, these fruits exhibit a wide range of pharmacological activities, including chemopreventive, analgesic, antilithogenic, antidiarrhoeal, antiallergic, antidiabetic, antihypertensive, hypoglycaemic, antimicrobial, antioxidant, antifungal, and antiviral properties [76].…”
Section: Chilhuacle Chili May Be More Than a Spicy Culinary Fruitmentioning
confidence: 99%
“…Finally, Capsicum fruits have an enantiomeric composition of phytochemicals. Many of these are chiral molecules that can exist in plants in different enantiomeric forms, such as the pepper aroma compound linalool [82], which occurs naturally in one enantiomeric form but experiences racemization during postharvest treatment [75,83]. In the case of the chilhuacle chili, all these chemical and pharmaceutical properties need to be studied in greater depth in a new research environment improved by the development and validation of new analytical protocols.…”
Section: Chilhuacle Chili May Be More Than a Spicy Culinary Fruitmentioning
confidence: 99%